Pengaruh Pembelajaran Fisika Menggunakan Metode Praktikum Terhadap Motivasi dan Hasil Belajar Kelas VII - Sri Maulida Ramadhani; Triwid Syafarotun Najah; Hadma Yuliani (Lembaga Bale Literasi, 2022)
Abstract This study aims to determine the effect of learning physics using the practicum method on the motivation and learning outcomes of class VII A MTs Berkah Palangka Raya Integrated MTs. The type of research used was aquasi-experimental designwith the type